THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH FOR SPECIFIC PURPOSES IN VOCATIONAL TRAINING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the role of Artificial Intelligence in teaching English for Specific Purposes (ESP) in vocational training institutions. The study highlights how AI-based technologies such as intelligent tutoring systems, speech recognition tools, adaptive learning platforms, and natural language processing applications enhance the effectiveness of ESP instruction. The research emphasizes the pedagogical benefits of AI, including personalized learning, increased learner motivation, autonomous skill development, and improved professional communication competence. The findings indicate that the integration of Artificial Intelligence into ESP teaching contributes to higher learning outcomes and better prepares vocational students for workplace communication.